Rýrnun grænmetis í smásöluverslun - Erla Björg Garðarsdóttir 1959- (2013)
Verkefnið er lokað til 3.5.2023. This research project, which is valued for 12 etcs, is a final project in Business finances and management at the University of Akureyri under the guidance of Jón Gestur Helgason. The waste of food occurs all around the world. From the part where the producer harvests the product until it is delivered to the seller and the consumer handles the product. The writer wanted to look at the deterioration in retail stores and see if there is a way to decrease the waste of fruits and vegetables. A survey was made at the process of this research where the customers of Fjarðarkaup were asked to answer, among other whether the layout and look of the product mattered when buying fruits and vegetables. Also a research was on how much deterioration of fruits and vegetables were occurring in Fjarðarkaup. The results of the research was that by monitoring closely the product that came from a supplier and send back those products that came damaged or ruined into the store, sort the vegetables and put them in to a 2.category and sell the product at a lower price you can lower the cost of deterioration by almost a half. It was also revealed from the costumers that the look and display of the product did matter. Keywords:waste, retail,employees, food display, service Þetta rannsóknarverkefni sem metið er til 12 eininga, er unnið sem lokaverkefni í Viðskiptafræði með áherslu á stjórnun og fjármálagreinar við Háskólann á Akureyri undir leiðsögn Jóns Gests Helgasonar. Sóun á matvælum á sér stað alls staðar í heiminum. Allt frá því að framleiðandi uppsker vöru þar til hún kemur til smásala og neytandi meðhöndlar vöruna. Skýrsluhöfundur vildi skoða rýrnun í smásöluverslun, og hvort hægt sé að minnka afföll af grænmeti og ávöxtum. Við vinnslu þessarar rannsóknar var gerður spurningalisti sem viðskiptavinir Fjarðarkaupa voru beðnir um að svara, meðal annars hvort framstilling og útlit vörunnar skipti máli við kaup á grænmeti og ávöxtum. Að auki var rannsakað hvað mikið af magni grænmetis og ávaxta fór ...